UPAYA GURU MENGIMPLEMENTASIKAN PENDIDIKAN MULTIKULTURAL DALAM MENJAGA KERUKUNAN ANTAR UMAT BERAGAMA PADA KELAS 2 DI SDN 12 BUKIT BATU - Sukma Nisa Aprilia; Zaka Hadikusuma Ramadan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the tendency of second-grade students at SD Negeri 12 Bukit Batu to choose friends based on religion, ethnicity, and social status, indicating the need for the implementation of multicultural education to strengthen tolerance and interreligious harmony. This descriptive qualitative study aimed to describe teachers’ efforts, challenges, and the impact of implementing multicultural education through observation, interviews, and documentation. The results showed that teachers implemented multicultural education through habituation of tolerance, role modeling, group work, and fostering mutual respect, despite challenges such as students’ limited understanding of tolerance, family environmental influences, and differences in students’ characteristics. The implementation had a positive impact on increasing mutual respect, cooperation, and reducing discriminatory friendship behavior among students.